1999
DOI: 10.1002/(sici)1096-8628(19990528)84:3<198::aid-ajmg5>3.0.co;2-w
|View full text |Cite
|
Sign up to set email alerts
|

Fully mutated and gray-zoneFRAXA alleles in Brazilian mentally retarded boys

Abstract: We used a non-isotopic polymerase chain reaction (PCR) technique for fragile X syndrome diagnosis to screen 256 mentally retarded boys who were selected randomly from special schools. Patients identified as pre- or full-mutation carriers were further investigated by Southern blot analysis with the StB12.3 probe. The PCR-based test identified five boys with the expanded allele and 17 other patients as carriers of either premutated or gray-zone alleles. The full mutation was confirmed in four cases after Souther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0
1

Year Published

1999
1999
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 16 publications
2
14
0
1
Order By: Relevance
“…Gray zone alleles were detected among patients as well as in the control group with frequencies of 3.03 and 2.70%, respectively (P = 0.38, Fisher exact test). Gray zone allele frequencies in these two groups were also similar to those previously reported (Haddad et al, 1999;Garcia Arocena et al, 2004;Toft et al, 2005). No premutation alleles in Figure 1.…”
Section: Resultssupporting
confidence: 89%
“…Gray zone alleles were detected among patients as well as in the control group with frequencies of 3.03 and 2.70%, respectively (P = 0.38, Fisher exact test). Gray zone allele frequencies in these two groups were also similar to those previously reported (Haddad et al, 1999;Garcia Arocena et al, 2004;Toft et al, 2005). No premutation alleles in Figure 1.…”
Section: Resultssupporting
confidence: 89%
“…Some studies 10,11 have reported an excess of these alleles in ID cohorts, suggesting a possible phenotypic effect in the intellectual functioning. Others, including the present study, have failed to replicate these results (listed in Table 3).…”
Section: Discussionmentioning
confidence: 99%
“…A study of patients with ID in the Brazilian population 10 reported a higher frequency of IA alleles in ID boys (6.3%) than in normal male controls (2.4%). In a similar study in a Southern England cohort of ID patients, 11 an unexpected excess of IA alleles of 4% was found compared with 2.4% for controls.…”
Section: Introductionmentioning
confidence: 97%
“…We used DNA from eight patients with fragile X syndrome, all confirmed by Southern blot analysis: five of these were ascertained in a screening study of mentally retarded boys in Brazil (Haddad et al, 1999), two were patients diagnosed at GENE and the other (NA06852) was obtained from the Coriell Mutant Cell Repository (Camden, NJ, USA). DNA samples from 42 normal controls were obtained from paternity testing cases at GENE.…”
Section: Patientsmentioning
confidence: 99%
“…The second drawback resulted from the "failure-toamplify" characteristic of the test that thus could not provide a definitive diagnosis of fragile X syndrome. Although not quite suitable for medical diagnosis, the PCR test proved to be a useful tool for fragile X syndrome screening in populations of mentally retarded males (Haddad et al, 1999).…”
Section: Introductionmentioning
confidence: 99%